Early works : - Wright, Richard (The Library of America, 1991)
Richard Wright's "Early Works" is a strong member of the set. As I worked my way through this volume, I found myself re-thinking questions I have put aside for a while, challenging attitudes that I have acquired as part of our zeitgeist. I did not find that much of interest in "Lawd Today!" and "Uncle Tom's Children," the first two selections in the volume. Perhaps I will take another look at them in the future. However, "Native Son" was a revelation to me, and I found it amazing.